CLINICAL EFFECTIVENESS OF NEUROTRANSMITTERS PATIENTS WITH PRIMARY GLAUCOMA VEGF INHIBITOR IN PATIENTS WITH CHOROIDAL NEOVASCULARIZATION CAUSED BY DEGENERATIVE MYOPIA - L. P. Danilova; V. V. Egorov; G. P. Smolyakova; L. P. Emanova; D. A. Povalyaeva (Oftalʹmologiâ, 2016)
Purpose. Morphological and functional evaluation of results of intravitreal injections of ranibizumab in treatment of choroidal neovascularization (CNV) caused by degenerative myopia (DM). patients and methods. The study included 32 patients (32 eyes) aged from 29 to 55 years with the CNV, developed due to the DM. They received 0.5 mg (0.05 ml) ranibizumab according to the standard. Indications for repeat intravitreal injections of ranibizumab were retention of the CNV activity or its recurrence. In addition to the standard ophthalmologic examination all patients were examined with fluorescein angiography (FAG) with photodetection of fundus picture and optical coherence tomography (OCT) of the retina (sizing subretinal neovascular membrane (SNM), evaluation of retinal foveal thickness (FCS). The study was conducted before the introduction of ranibizumab, monthly during the first 6 months after surgery, and then, in the absence of symptoms of CNV activity, every 2-3 months. The total follow-up was 12 months. results. the transition the CNV in inactive form according to FAG was observed in 25 people (78.1%) was observed after 1 month (single injection of ranibizumab). The angiographic signs of CNV activity remained after the first injection in 7 patients (21/9%). They received second intravitreal injection of ranibizumab. After 3 months from the beginning of observation according to FAG and OCT data relapse of activity of myopic CNV occurred in 5 patients (15.6%) after a single injection, and in 2 patients (6.3%) — after a double injection of ranibizumab. After 6 months according to FAG disappearance of pathological leakage of the dye was diagnosed in 87.5% of patients (28 eyes). After 12 months follow-up all 32 patients had remission of the pathological process with no evidence of CNV activity with formation of local subretinal fibrosis with choriocapillaries atrophy. Conclusions. It took from 1 to 3 (average 1.58) injections of ranibizumab to transfer the active phase of the CNV in inactive. Complete inhibition of the growth and activity of myopic CNV was accompanied by positive morphological and functional results, which led to a significant improvement in visual acuity in 2 times at the observation period of 12 months.